ANALISIS KINERJA PABRIK TEH HITAM Ã¢â‚¬Å“PAHIT MADUÃ¢â‚¬Â - djawardi, djawardi; gunawan, yustiar (Badan Pengkajian dan Penerapan Teknologi, 2011)
The business unit's black tea processing of Perkebunan Nusantara suffered a loss of approximately Rp.60 billion. This is caused by the failure to achieve the quality and quantity of production which has been targeted by the management. Black tea processing factory